A comparative study of vertical stabilities in the Arabian Sea and Bay of Bengal (MAUSAM, 1981)
Stabilities in the upper 300 m in the Arabian Sea and the Bay of Bengal are computed and presented seasonwise. The water column in the Bay of Bengal is more strongly stratified than that in the Arabian Sea. These studies suggest that the vertical transfer of subsurface nutrients into the surface layer in the Bay of Bengal is greatly inhibited.